High-temperature-resistant high-strength mullite aerogel composite material and preparation method thereof

Through the method of composite of mesoporous silicon-aluminum molecular sieve framework with a three-dimensional network of mullite particles, a high-temperature and high-strength mullite aerogel composite material was prepared, which solved the problems of phase change and structural collapse of alumina aerogel at high temperatures, and achieved efficient high-temperature heat insulation and excellent mechanical properties.

CN119633698APending Publication Date: 2025-03-18AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411829889.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing alumina aerogels will undergo phase change and structural collapse when high temperatures exceed 1200°C, resulting in a decrease in mechanical properties. The application of common oxide aerogels in the field of high temperatures is limited.

Method used

By using the method of composite of mesoporous silicon-aluminum molecular sieve framework with a three-dimensional network of mullite particles, a high temperature and high strength mullite aerogel composite material is prepared. The method includes preparing a silicon-aluminum sol, mixing of silicon-aluminum molecular sieve solutions, adding a coagulant, alcohol replacement and supercritical drying, and calcining treatment to form a mullite aerogel composite material.

Benefits of technology

It has achieved excellent thermal insulation, oxidation resistance and high strength under high temperature conditions, and the material has a low density, large specific surface area, and a temperature resistance of up to 1400℃. It is suitable for high-temperature thermal insulation, catalysis and adsorption fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633698A_ABST
    Figure CN119633698A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant high-strength mullite aerogel composite material and a preparation method thereof. The mullite aerogel composite material comprises a silicon-aluminum molecular sieve skeleton structure and a mullite particle three-dimensional network combined with the silicon-aluminum molecular sieve skeleton structure, the framework structure of the silicon-aluminum molecular sieve is a framework structure formed by penetrating and lapping a silicon dioxide molecular sieve or a framework structure formed by penetrating and lapping a molecular sieve formed by silicon dioxide and aluminum oxide. The preparation method comprises the following steps: preparing silica-alumina sol and a silica-alumina molecular sieve solution, uniformly mixing the silica-alumina sol and the silica-alumina molecular sieve solution to obtain silica-alumina composite sol, then adding a coagulant for gelling and aging treatment to obtain silica-alumina composite gel, and then carrying out alcohol replacement and supercritical drying treatment to obtain silica-alumina composite aerogel; and calcining the silicon-aluminum composite aerogel to obtain the mullite aerogel composite material. The temperature resistance of the oxide aerogel in the air is improved to 1400 DEG C, and the oxide aerogel has great application prospects in the fields of high-temperature heat insulation, industrial high-temperature catalysis or adsorption and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation technology of aerogel materials, and in particular to a high-temperature resistant and high-strength mullite aerogel composite material and a preparation method thereof. Background Art

[0002] Aerogel is a nanoporous material with high specific surface area, ultra-low density and high porosity (>95%). Its excellent thermal insulation performance has enabled it to be successfully applied in the fields of thermal insulation, chemical industry and energy-saving buildings, and has broad application prospects. With the rapid development of the field of thermal insulation, the demand for high-temperature resistant aerogels is becoming more and more urgent. At present, the two most common oxide aerogel materials are silica and alumina aerogels. Among them, silica aerogel will sinter at high temperatures exceeding 650°C, resulting in the collapse of the nanopore structure and the degradation of performance. In contrast, alumina aerogel has better thermal stability and can remain stable at temperatures up to 1000°C. However, when the temperature exceeds 1200°C, the crystal form will change and cause its structural collapse and macroscopic powder and slag falling, which will increase the thermal conductivity and reduce the mechanical properties. Therefore, the application of common oxide aerogels in high temperature fields (>1200°C) is limited.

[0003] In order to solve the problems of poor mechanical properties of alumina, such as phase change and structural collapse at high temperatures, researchers have adopted methods such as element or oxide doping modification and particle or fiber reinforcement to alleviate and improve. Studies have shown that the high-temperature phase change of alumina can be significantly inhibited by doping with silicon oxide, especially under high temperature conditions, the alumina phase can be transformed into the mullite phase. Since the temperature resistance of mullite is better than that of alumina, mullite aerogel can be prepared by adjusting the content ratio of alumina to silicon oxide and heat treating at a certain temperature. Patents CN 109678519 B and CN 104291781 B respectively use supercritical modification and high-temperature superfluid modification methods to prepare 1200°C resistant silicon-aluminum composite aerogels. The shrinkage rate after 1200°C treatment is within 10%, but the mechanical properties of the aerogel material are not mentioned, and the preparation process is complicated, making it difficult to achieve large-scale production. Xiaodong Wu et al. (CXSu, TDKoudama, XDWu, et al. Rational design of anovel mullite aerogel with extremely high mechanical strength and anti-oxidation behavior for advanced thermal protection in extreme environments, J.Eur.Ceram.Soc.44 (2024) 1761-1771.) introduced a phenolic resin network into Al2O3-SiO2 aerogel and prepared a new type of carbon-mullite aerogel by supercritical carbon dioxide drying and high-temperature sintering (>1200°C). The aerogel has a typical "pearl necklace" three-dimensional network structure, with a specific surface area and compressive strength of up to 481m 2 / g and 15.5MPa, and after 10min in butane flame (1300℃), its macroscopic shape did not change, indicating that it has excellent ablation resistance and thermal stability and excellent performance. However, the system contains a large amount of carbon components and the material's antioxidant performance is weak, which hinders its application under extreme high temperature oxygen-containing conditions (>800℃). Patents CN 109081673 B, CN 116023165A, CN 104291781 B and Huijun Yu et al. (JHYu, ZWTong, BJZhang, et al. Thermal radiation shielded, high strength, fire resistant fiber / nanorod / aerogel composites fabricated byin-situ growth of TiO2 nanorods for thermal insulation, Chem. Eng. J.418 (2021) 129342.) used whiskers and micro-nanofibers as reinforcement phases to prepare high-temperature resistant silicon-aluminum composite aerogels with both mechanical properties, but the reinforcement phase has a large density and a small specific surface area, which increases the solid-phase thermal conductivity to a certain extent, resulting in a significant increase in the thermal conductivity. Patent CN 114132940B uses aluminum-containing two-dimensional porous, crystalline metal covalent organic framework materials and silicate as aluminum and silicon sources, respectively, and uses freeze drying and 1200℃ air calcination to prepare high-temperature resistant mullite aerogel. The macroscopic structure of the aerogel material is complete and has ultra-light properties (26mg / cm 3 ), but the heat treatment temperature (>1200℃) required for mullite in the system is relatively high, and the mesoporous framework structure is difficult to retain, resulting in a small specific surface area. In addition, the pore size formed by the freeze-drying method is highly connected and large, the thermal insulation performance is poor, and the aluminum source used is extremely expensive, making it difficult to mass-produce and apply. Therefore, it is urgent to develop mullite aerogel materials that are both resistant to high temperatures, have low thermal conductivity and high strength. Summary of the invention

[0004] The mullite aerogel materials currently using fibers, whiskers and particles as reinforcement phases have the problems of high mullite conversion temperature, large reinforcement phase density, small specific surface area and poor temperature resistance. The purpose of the present invention is to provide a method for preparing a mullite aerogel composite material. The mullite aerogel material obtained by the preparation method has a high specific surface area and excellent high-temperature oxidation resistance and low thermal conductivity, and has broad application prospects in the fields of high-temperature thermal insulation, catalysis and adsorption.

[0005] Another object of the present invention is to provide a mullite aerogel composite material, wherein the aerogel material is a composite of a mesoporous silica-alumina molecular sieve skeleton and a mullite particle three-dimensional network.

[0006] The purpose of the present invention is achieved through the following technical solutions.

[0007] A high-temperature resistant and high-strength mullite aerogel composite material comprises a silica-alumina molecular sieve skeleton structure and a three-dimensional network of mullite particles combined with the silica-alumina molecular sieve skeleton structure; the silica-alumina molecular sieve skeleton structure is a skeleton structure formed by interlacing silica molecular sieves, or a skeleton structure formed by interlacing molecular sieves composed of silica and alumina.

[0008] In the above technical solution, the material of the mullite particles is mullite, or alumina and mullite, or silicon oxide and mullite.

[0009] In the above scheme, the size (particle diameter) of the mullite particles is 30 to 450 nm, preferably 40 to 100 nm.

[0010] A method for preparing a high-temperature resistant and high-strength mullite aerogel composite material comprises the following steps:

[0011] preparing alumina-silica sol;

[0012] preparing a silicon-alumina molecular sieve solution;

[0013] The silica-alumina sol and the silica-alumina molecular sieve solution are uniformly mixed to obtain a silica-alumina composite sol;

[0014] Adding a coagulant to the silica-alumina composite sol to perform gelation and aging treatment to obtain a silica-alumina composite gel;

[0015] The silica-alumina composite gel is subjected to alcohol replacement and supercritical drying to obtain a silica-alumina composite aerogel;

[0016] The silicon-aluminum composite aerogel is calcined to obtain a mullite aerogel composite material.

[0017] Each step in the above method is described in detail below.

[0018] Step 1, preparation of silica-alumina sol;

[0019] Aluminum alkoxide and solvent are added to a reaction container, heated to a certain temperature by a heating device, stirred at a constant temperature for a certain period of time to mix evenly, and then aluminum sol is obtained after clarification, and the obtained aluminum sol is cooled to room temperature; a certain amount of silicon precursor is added thereto, and then mixed with an acid catalyst, and after being fully stirred for a certain period of time, silicon aluminum sol is obtained.

[0020] In the step 1, the solvent is any one of ethanol, isopropanol, acetone or n-butanol, the constant temperature stirring for a certain period of time is 30 to 70° C., and the stirring time is 6 to 12 hours.

[0021] In the step 1, the aluminum alkoxide is any one of aluminum sec-butoxide and aluminum isopropoxide, and the mass ratio of the aluminum alkoxide to the solvent is (1-4):10.

[0022] In step 1, the silicon precursor is at least one of tetramethyl silicate, tetraethyl silicate, tetraisopropyl silicate, tetrabutyl silicate, and tetraphenyl silicate.

[0023] In the step 1, the molar ratio of the aluminum alkoxide to the silicon precursor is (1-3):1.

[0024] In step 1, the acid catalyst is a nitric acid solution, the molar concentration of the nitric acid solution is 0.5-2 mol / L, the molar ratio of aluminum alkoxide to the acid catalyst is 2:(1-1.5), and the stirring time for the sufficient stirring for a certain period of time is 8-24 hours.

[0025] Step 2, preparation of a silicon-alumina molecular sieve solution;

[0026] The silicon-aluminum molecular sieve, the modified additive and the solvent are ultrasonically treated and uniformly mixed to obtain a silicon-aluminum molecular sieve solution.

[0027] In the step 2, the silica-alumina molecular sieve includes one of SBA-15, MCM-41 and ZSM-5 or a mixture thereof.

[0028] In the step 2, the modifying additive includes one or a mixture of V2O5, MnO2 and CoO.

[0029] In step 2, the mass ratio of the molecular sieve, the modification additive and the solvent is (10-20):(1-5):100.

[0030] Step 3, preparation of silicon-alumina molecular sieve / Al2O3-SiO2 wet gel;

[0031] This step is to evenly mix the silica-alumina sol prepared in step 1 with the silica-alumina molecular sieve solution in step 2 to obtain a silica-alumina composite sol, add a coagulant to the composite sol for dispersion, then pour the sol into a molding mold, seal it and let it stand to obtain a wet gel of the silica-alumina molecular sieve composite silica-alumina sol.

[0032] In step 3, the volume ratio of the silica-alumina sol to the silica-alumina molecular sieve solution is (5-12):1.

[0033] In step 3, the coagulant is propylene oxide or epichlorohydrin, or a mixture of the two.

[0034] In the step 3, the molar ratio of the aluminum alkoxide to the coagulant is 1:(5-12).

[0035] In step 3, the sealing is left to stand for 3 to 10 hours.

[0036] Step 4, preparation of silicon aluminum molecular sieve / Al2O3-SiO2 aerogel:

[0037] The wet gel block in step 3 is added with an aging liquid, and replaced in an oven at 30-75°C for 5-14 times, with each aging time being 24 hours, to obtain a silicon-aluminum composite gel; the obtained gel block is taken out from the aging liquid for alcohol replacement, and then placed in an autoclave, heated and pressurized for supercritical drying to obtain a high-strength block silicon-aluminum composite aerogel.

[0038] In step 4, the aging liquid is one of ethanol, methanol, acetone, or isopropanol, or a mixture thereof.

[0039] In step 4, the supercritical drying method is a carbon dioxide supercritical drying method: carbon dioxide is used as the drying medium, the reaction temperature is 45-65° C., the pressure in the high-pressure reactor is 8-12 MPa, the degassing rate is 4-16 L / min, and the drying time is 5-14 h.

[0040] Step 5, preparation of mullite aerogel composite material

[0041] The composite aerogel obtained in step 4 is calcined (roasted) in an air atmosphere to prepare a bulk silica-alumina molecular sieve / mullite aerogel composite material.

[0042] In step 5, the temperature of the air atmosphere heat treatment is 1000-1100° C., the heating rate is 2-8° C. / min, and the heat preservation time is 1-4 hours.

[0043] The mullite aerogel composite material is obtained by the above preparation method.

[0044] The above-mentioned high-temperature resistant, high-strength and high-surface-area mullite aerogel composite material is used in high-temperature insulation, industrial high-temperature catalysis or adsorption materials.

[0045] Compared with the prior art, the present invention has the following advantages:

[0046] (1) In-situ skeleton reinforcement of silica-alumina molecular sieve. In this patent, silica-alumina molecular sieve with good thermal stability is used as a reinforcing material. Due to its rich mesoporous structure, the density and thermal conductivity of the material are very low. When mixed with silica-alumina sol, it can be evenly dispersed and suspended in the sol for a long time until gelation, and a block aerogel with good uniformity and the original density of pure aerogel can be prepared. At the same time, in the sol-gel process, the silica-alumina molecular sieve cross exists as a skeleton, and hydrogen bonds are used to make the silica-alumina particles strongly adhere and spread and grow into a three-dimensional network structure, which has a reinforcing effect on the aerogel. During the heat treatment process, the silica-alumina molecular sieve, as a partial silica-alumina source, produces a strong physical bond, thereby avoiding cracking and damage of the material due to shrinkage, improving the integrity, compressive strength and temperature resistance of the block material molding, while maintaining the low density, high specific surface area and excellent thermal insulation performance of the silica-alumina aerogel.

[0047] (2) Simple process. The sol-gel method is used to introduce aluminum source, silicon source and modification additives at the same time, and through the subsequent supercritical drying and heat treatment process, compared with the existing technology, under the action of modifiers such as CoO and V2O5, the silicon source and aluminum source can complete the mullite reaction at a lower temperature, with a smaller degree of shrinkage, thereby finally producing an ultra-light and low thermal conductivity block mullite aerogel composite material.

[0048] (3) The mullite aerogel composite material prepared by this method is in a complete block, which further improves the temperature resistance of the oxide aerogel. The temperature resistance in air is increased to 1400°C. In addition, the raw materials are easily available and the preparation process is simple, which is conducive to industrial production. This has positive significance for realizing the application of mullite aerogel materials in high-temperature insulation, industrial high-temperature catalysis or adsorption materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0050] Figure 1 The present invention is a process roadmap for preparing the high temperature resistant and high strength mullite aerogel composite material;

[0051] Figure 2 This is a physical picture of the mullite aerogel composite material prepared in Example 1;

[0052] Figure 3 are scanning electron microscope photos, wherein (a) is a scanning electron microscope photo of SBA-15; (b) is a scanning electron microscope photo of the mullite aerogel composite material prepared in Example 1. DETAILED DESCRIPTION

[0053] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0054] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0055] The present invention provides a method for preparing a high-temperature resistant and high-strength mullite aerogel composite material, the process of which is as follows: Figure 1 As shown, the main steps include: preparing a silica-alumina sol; preparing a silica-alumina molecular sieve solution; uniformly mixing the silica-alumina sol and the silica-alumina molecular sieve solution to obtain a silica-alumina composite sol; adding a coagulant to the silica-alumina composite sol for gelation and aging treatment to obtain a silica-alumina composite gel; subjecting the silica-alumina composite gel to alcohol replacement and supercritical drying treatment to obtain a silica-alumina composite aerogel; and calcining the silica-alumina composite aerogel to obtain a mullite aerogel composite material.

[0056] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0057] The models of the instruments involved in the following embodiments are as follows: 5.0 kV field emission scanning electron microscope (SEM, TDCLS-S4800, Japan), universal testing machine (CMT4303, Meister Industrial Systems, China), specific surface area and pore size analyzer (Nova 2200e, Quanta-chrome Instruments, USA), thermal conductivity tester (TC3000, XIATECH Instrument, China)

[0058] Embodiment 1:

[0059] The ingredients are prepared with the amount of SBA-15 added (mass of SBA-15) according to the weight ratio of (mass of SBA-15 + mass of deionized water) = 1:10 and the molar ratio of aluminum isopropoxide:ethyl orthosilicate = 3:1.

[0060] 3g of aluminum isopropoxide and 30g of ethanol were added to the reaction vessel, heated to 40°C in a water bath, stirred at constant temperature for 10h, mixed and clarified to obtain aluminum sol, cooled to room temperature, added 1.08g of tetraethyl orthosilicate, continued stirring for 3h, then added 3mL of nitric acid solution (2mol / L), stirred for 12h to obtain silica-alumina sol. 10g of SBA-15 and 0.5g of CoO were added to 100g of water, ultrasonically treated for 20min and magnetically stirred for 60min, and mixed to obtain SBA-15 solution. 1mL of SBA-15 solution was added to 10mL of silica-alumina composite sol, magnetically stirred for 2h to mix evenly, and then propylene oxide was added in a molar ratio of aluminum to propylene oxide of 1:8 and stirred for 10min to obtain silica-alumina composite sol. The composite sol was poured into a mold and gelled in an oven at 45°C. After the gel is placed for 2 hours, ethanol aging liquid is added and replaced in an oven at 30°C for 5 times, each time for 12 hours. The wet gel is then replaced with alcohol and subjected to CO2 supercritical drying treatment, with a supercritical reaction temperature of 50°C. The reactor pressure is 10MPa, the degassing rate is 5L / min, and the SBA-15 composite aluminum silicate aerogel is obtained after a drying time of 12 hours. The composite aerogel is heat treated at 1050°C in an air atmosphere, with a heating rate of 2°C / min and a holding time of 2 hours, thereby obtaining a blocky mullite aerogel composite material.

[0061] After testing, the density of the block high temperature resistant mullite aerogel composite material is 0.069g / cm 3 , with a specific surface area of ​​294m 2 / g, and the room temperature thermal conductivity is 0.026W·m -1 ·K -1 , compressive strength is 4.32MPa, and temperature resistance can reach 1400℃.

[0062] from Figure 2 It can be seen from the figure that after heat treatment, the shape of the obtained mullite aerogel composite material is controllable and no sintering shrinkage occurs. Figure 3 It can be seen that SBA-15 is distributed more evenly and its microstructure is still in the morphology of nano-aerogel particles.

[0063] Embodiment 2:

[0064] The ingredients were prepared with the amount of SBA-15 added (mass of SBA-15) according to the weight ratio of (mass of SBA-15 + mass of deionized water) = 1:20.

[0065] 3g of aluminum isopropoxide and 30g of ethanol were added to the reaction vessel, heated to 40°C in a water bath, stirred at constant temperature for 10h, mixed and clarified to obtain aluminum sol, cooled to room temperature, added 1.08g of ethyl orthosilicate, continued stirring for 3h, then added 3mL of nitric acid solution (2mol / L), stirred for 12h to obtain silica-alumina sol. 5g of SBA-15 and 0.5g of CoO were added to 100g of water, ultrasonically treated for 20min and magnetically stirred for 60min, and mixed to obtain SBA-15 solution. 1mL of SBA-15 solution was added to 10mL of silica-alumina composite sol, magnetically stirred for 2h to mix evenly, and then propylene oxide was added in a molar ratio of aluminum to propylene oxide of 1:8 and stirred for 10min to obtain silica-alumina composite sol. The composite sol was poured into a mold and gelled in an oven at 45°C. After the gel is placed for 2 hours, ethanol aging liquid is added and replaced in an oven at 30°C for 5 times, each time for 12 hours. The wet gel is then replaced with alcohol and subjected to CO2 supercritical drying treatment, with a supercritical reaction temperature of 50°C. The reactor pressure is 10MPa, the degassing rate is 5L / min, and the SBA-15 composite aluminum silicate aerogel is obtained after a drying time of 12 hours. The composite aerogel is heat treated at 1050°C in an air atmosphere, with a heating rate of 2°C / min and a holding time of 2 hours, thereby obtaining a blocky mullite aerogel composite material.

[0066] After testing, the density of the block high temperature resistant mullite aerogel composite material is 0.073g / cm 3 , with a specific surface area of ​​186m 2 / g, and the room temperature thermal conductivity is 0.028W·m -1 ·K -1 , the compressive strength is 3.43MPa.

[0067] Embodiment 3:

[0068] No CoO is added to the SBA-15 solution

[0069] 3g of aluminum isopropoxide and 30g of ethanol were added to the reaction vessel, heated to 40°C in a water bath, stirred at constant temperature for 10h, mixed and clarified to obtain aluminum sol, cooled to room temperature, added 1.08g of ethyl orthosilicate, continued stirring for 3h, then added 3mL of nitric acid solution (2mol / L), stirred for 12h to obtain silica-alumina sol. 10g of SBA-15 was added to 100g of water, and after ultrasonic treatment for 20min and magnetic stirring for 60min, the SBA-15 solution was obtained after mixing evenly. 1mL of SBA-15 solution was added to 10mL of silica-alumina composite sol, magnetically stirred for 2h to mix evenly, and then propylene oxide was added in a molar ratio of aluminum to propylene oxide of 1:8 and stirred for 10min to obtain silica-alumina composite sol. The composite sol was poured into a mold and gelled in an oven at 45°C. After gelling, the ethanol aging solution was added after standing for 2h, and replaced 5 times in an oven at 30°C, each time for 12h. The wet gel was then replaced with alcohol and subjected to CO2 supercritical drying treatment, with a supercritical reaction temperature of 50°C. The reactor pressure was 10MPa, the degassing rate was 5L / min, and the drying time was 12h to obtain SBA-15 composite aluminum silicate aerogel. The composite aerogel was heat treated at 1050°C in an air atmosphere, with a heating rate of 2°C / min and a holding time of 2h, thereby obtaining a blocky mullite aerogel composite material.

[0070] After testing, the density of the block high temperature resistant mullite aerogel composite material is 0.063g / cm 3 , with a specific surface area of ​​265m 2 / g, and the room temperature thermal conductivity is 0.024W·m -1 ·K -1 , the compressive strength is 3.91MPa.

[0071] Embodiment 4:

[0072] Heat treatment temperature in air atmosphere is 950℃

[0073] 3g of aluminum isopropoxide and 30g of ethanol were added to the reaction vessel, heated to 40°C in a water bath, stirred at constant temperature for 10h, mixed and clarified to obtain aluminum sol, cooled to room temperature, added 1.08g of tetraethyl orthosilicate, continued stirring for 3h, then added 3mL of nitric acid solution (2mol / L), stirred for 12h to obtain silica-alumina sol. 10g of SBA-15 and 0.5g of CoO were added to 100g of water, ultrasonically treated for 20min and magnetically stirred for 60min, and mixed to obtain SBA-15 solution. 1mL of SBA-15 solution was added to 10mL of silica-alumina composite sol, magnetically stirred for 2h to mix evenly, and then propylene oxide was added in a molar ratio of aluminum to propylene oxide of 1:8 and stirred for 10min to obtain silica-alumina composite sol. The composite sol was poured into a mold and gelled in an oven at 45°C. After the gel is placed for 2 hours, ethanol aging liquid is added and replaced in an oven at 30°C for 5 times, each time for 12 hours. The wet gel is then replaced with alcohol and subjected to CO2 supercritical drying treatment, with a supercritical reaction temperature of 50°C. The reactor pressure is 10MPa, the degassing rate is 5L / min, and the SBA-15 composite aluminum silicate aerogel is obtained after a drying time of 12 hours. The composite aerogel is heat treated at 950°C in an air atmosphere, with a heating rate of 2°C / min and a holding time of 2 hours, thereby obtaining a blocky mullite aerogel composite material.

[0074] After testing, the density of the block high temperature resistant mullite aerogel composite material is 0.058g / cm 3 , with a specific surface area of ​​346m 2 / g, and the room temperature thermal conductivity is 0.024W·m -1 ·K -1 , the compressive strength is 2.95MPa.

[0075] Embodiment 5:

[0076] Aluminum isopropoxide: ethyl orthosilicate = 2:1 molar ratio for mixing

[0077] 2g of aluminum isopropoxide and 30g of ethanol were added to the reaction vessel, heated to 40°C in a water bath, stirred at constant temperature for 10h, mixed and clarified to obtain aluminum sol, cooled to room temperature, added 1.08g of ethyl orthosilicate, continued stirring for 3h, then added 3mL of nitric acid solution (2mol / L), stirred for 12h to obtain silica-alumina sol. 10g of SBA-15 and 0.5g of CoO were added to 100g of water, ultrasonically treated for 20min and magnetically stirred for 60min, and mixed to obtain SBA-15 solution. 1mL of SBA-15 solution was added to 10mL of silica-alumina composite sol, magnetically stirred for 2h to mix evenly, and then propylene oxide was added in a molar ratio of aluminum to propylene oxide of 1:8 and stirred for 10min to obtain silica-alumina composite sol. The composite sol was poured into a mold and gelled in an oven at 45°C. After the gel is placed for 2 hours, ethanol aging liquid is added and replaced in an oven at 30°C for 5 times, each time for 12 hours. The wet gel is then replaced with alcohol and subjected to CO2 supercritical drying treatment, with a supercritical reaction temperature of 50°C. The reactor pressure is 10MPa, the degassing rate is 5L / min, and the SBA-15 composite aluminum silicate aerogel is obtained after a drying time of 12 hours. The composite aerogel is heat treated at 1050°C in an air atmosphere, with a heating rate of 2°C / min and a holding time of 2 hours, thereby obtaining a blocky mullite aerogel composite material.

[0078] After testing, the density of the block high temperature resistant mullite aerogel composite material is 0.055g / cm 3 , with a specific surface area of ​​308m 2 / g, and the room temperature thermal conductivity is 0.025 W·m -1 ·K -1 , the compressive strength is 4.53MPa.

[0079] Embodiment 6:

[0080] No SBA-15 is added to the ingredients

[0081] 3g of aluminum isopropoxide and 30g of ethanol were added to the reaction vessel, heated to 40°C in a water bath, stirred at constant temperature for 10h, mixed and clarified to obtain aluminum sol, cooled to room temperature, added 1.08g of ethyl orthosilicate, continued stirring for 3h, then added 3mL of nitric acid solution (2mol / L), stirred for 12h to obtain silica-alumina sol. 0.5g of CoO was added to 100g of water, and after ultrasonic treatment for 20min and magnetic stirring for 60min, the SBA-15 solution was obtained after mixing. 1mL of SBA-15 solution was added to 10mL of silica-alumina composite sol, magnetically stirred for 2h to mix evenly, and then propylene oxide was added in a molar ratio of aluminum to propylene oxide of 1:8 and stirred for 10min to obtain silica-alumina composite sol. The composite sol was poured into a mold and gelled in an oven at 45°C. After gelling, the ethanol aging solution was added after standing for 2h, and replaced 5 times in an oven at 30°C, each time for 12h. The wet gel was then replaced with alcohol and subjected to CO2 supercritical drying treatment, with a supercritical reaction temperature of 50°C. The reactor pressure was 10MPa, the degassing rate was 5L / min, and the drying time was 12h to obtain SBA-15 composite aluminum silicate aerogel. The composite aerogel was heat treated at 1050°C in an air atmosphere, with a heating rate of 2°C / min and a holding time of 2h, thereby obtaining a blocky mullite aerogel composite material.

[0082] After testing, the density of the block high temperature resistant mullite aerogel composite material is 0.083g / cm 3 , with a specific surface area of ​​184m 2 / g, and the room temperature thermal conductivity is 0.037W·m -1 ·K -1 , the compressive strength is 3.46MPa.

[0083] Summary: Comparison between Example 1 and Example 2, SBA-15 is used as the skeleton support material of aerogel, and the effect of the addition ratio on the compressive strength is: within a certain range of proportions, the greater the addition ratio, the higher the compressive strength; comparison between Example 1 and Example 3, the effect of adding a modifier on the mullite sintering behavior is: the introduction of CoO reduces the mullite conversion temperature and improves the compressive strength and temperature resistance of aerogel; comparison between Example 1 and Example 4, the heat treatment temperature is different, and the effect of the heat treatment temperature on the performance of aerogel materials is: within a certain temperature range, the higher the temperature, the higher the compressive strength. The larger the value, the more complete the mullite conversion; in comparison between Example 1 and Example 5, the different amounts of silicon added, the effect of silicon oxide on the sintering behavior of the composite material is: within a certain range, the more SiO2 is added, the more uniform the morphology of particle accumulation, the larger the specific surface area, the higher the compressive strength, and the better the thermal insulation performance; in comparison between Example 1 and Example 6, the effect of SBA-15 addition on the sintering behavior of the composite material is: within a certain range, the more SBA-15 is added, the smaller the heat treatment shrinkage, the smaller the density, the larger the specific surface area, the higher the compressive strength, and the better the thermal insulation performance.

[0084] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high temperature resistant and high strength mullite aerogel composite material, characterized in that: It includes a silica-alumina molecular sieve skeleton structure and a three-dimensional network of mullite particles combined with the silica-alumina molecular sieve skeleton structure; the silica-alumina molecular sieve skeleton structure is a skeleton structure formed by the interweaving of silica molecular sieves, or a skeleton structure formed by the interweaving of molecular sieves composed of silica and alumina.

2. The high temperature resistant and high strength mullite aerogel composite material according to claim 1, characterized in that: The material of the mullite particles is mullite, or alumina and mullite, or silicon oxide and mullite; the particle size of the mullite particles is 30-450nm.

3. A method for preparing a high temperature resistant and high strength mullite aerogel composite material, characterized in that: The following steps are involved: preparing a silica-alumina sol; preparing a silicon-alumina molecular sieve solution; The silica-alumina sol and the silica-alumina molecular sieve solution are uniformly mixed to obtain a silica-alumina composite sol; Adding a coagulant to the silica-alumina composite sol to perform gelation and aging treatment to obtain a silica-alumina composite gel; The silica-alumina composite gel is subjected to alcohol replacement and supercritical drying to obtain a silica-alumina composite aerogel; The silicon-aluminum composite aerogel is calcined to obtain a mullite aerogel composite material.

4. The method according to claim 3, characterized in that The method for preparing the silica-alumina sol comprises: Aluminum alkoxide and solvent are added to a reaction vessel, stirred at a temperature of 30 to 70° C. for 6 to 12 hours, mixed evenly and clarified to obtain aluminum sol, to which a silicon precursor is added, and then mixed with an acid catalyst, and stirred sufficiently for 8 to 24 hours to obtain silicon-aluminum sol; The solvent is any one of ethanol, isopropanol, acetone or n-butanol; The aluminum alkoxide is any one of aluminum sec-butoxide and aluminum isopropoxide, and the mass ratio of the aluminum alkoxide to the solvent is (1-4):10; The silicon precursor is at least one of tetramethyl silicate, tetraethyl silicate, tetraisopropyl silicate, tetrabutyl silicate and tetraphenyl silicate; The molar ratio of the aluminum alkoxide to the silicon precursor is (1-3):1; The acid catalyst is a nitric acid solution, the molar concentration of the nitric acid solution is 0.5-2 mol / L, and the molar ratio of the aluminum alkoxide to the acid catalyst is 2:(1-1.5).

5. The method according to claim 4, characterized in that The method for preparing the silicon-aluminum molecular sieve solution comprises: The silicon-aluminum molecular sieve, the modified additive and the solvent are ultrasonically treated and uniformly mixed to obtain a silicon-aluminum molecular sieve solution; The silicon-aluminum molecular sieve includes one of SBA-15, MCM-41 and ZSM-5 or a mixture thereof; The modifying additive includes one or a mixture of V2O5, MnO2 and CoO; The mass ratio of the molecular sieve, the modified additive and the solvent is (10-20):(1-5):

100.

6. The method according to claim 5, characterized in that The silica-alumina sol and the silica-alumina molecular sieve solution are mixed evenly, wherein the volume ratio of the silica-alumina sol to the silica-alumina molecular sieve solution is (5-12):

1.

7. The method according to claim 6, characterized in that The step of adding a coagulant to the silica-alumina composite sol for gelation and aging treatment comprises: Adding a coagulant to the silica-alumina composite sol for dispersion, then pouring the sol into a molding mold, sealing it and letting it stand, to obtain a wet gel of the silica-alumina molecular sieve composite silica-alumina sol; The wet gel block is added with an aging solution, and replaced 5 to 14 times in an oven at 30 to 75° C., with each aging time being 24 hours, to obtain a silicon-aluminum composite gel; The coagulant is one or a mixture of propylene oxide or epichlorohydrin; The molar ratio of the aluminum alkoxide to the coagulant is 1:(5-12); The sealing and standing time is 3 to 10 hours; The aging liquid is one of ethanol, methanol, acetone, isopropanol or a mixture thereof.

8. The method according to claim 3, characterized in that The supercritical drying process uses carbon dioxide as a drying medium, the reaction temperature is 45-65° C., the pressure in the high-pressure reactor is 8-12 MPa, the degassing rate is 4-16 L / min, and the drying time is 5-14 h.

9. The method according to claim 3, characterized in that: The calcination treatment is carried out in an air atmosphere, the calcination temperature is 1000-1100° C., the heating rate is 2-8° C. / min, and the heat preservation time is 1-4 hours.

10. Use of the high temperature resistant and high strength mullite aerogel composite material prepared by the method according to any one of claims 3 to 9 in high temperature thermal insulation materials, industrial high temperature catalytic carrier materials or adsorption materials.

Citation Information

Patent Citations

  • A preparation method of silicon-aluminum composite airgel material with high temperature resistance and good formability

    CN104291781B

  • A fiber-reinforced alumina aerogel composite material and its preparation method

    CN109081673B

  • A high-temperature pressure sensor based on polymer precursor ceramics

    CN109678519B

  • A method for preparing ultralight, high-temperature resistant bulk mullite aerogel

    CN114132940B

  • Preparation method of nano silicon dioxide fiber reinforced aluminum oxide aerogel composite material

    CN116023165A